Floquet-induced superfluidity with periodically modulated interactions of two-species hardcore bosons in a one-dimensional optical lattice - Tao Wang (汪涛); Shijie Hu (胡时杰); Sebastian Eggert; Michael Fleischhauer; Axel Pelster; Xue-Feng Zhang (张学锋) (Physical Review Research, 2020)
We consider two species of hard-core bosons with density-dependent hopping in a one-dimensional optical lattice, for which we propose experimental realizations using time-periodic driving. The quantum phase diagram for half-integer filling is determined by combining different advanced numerical simulations with analytic calculations. We find that a reduction of the density-dependent hopping induces a Mott-insulator to superfluid transition. For negative hopping, a gauge-dressed superfluid state is found where one species induces a gauge phase of the other species, which leads to a superfluid phase of gauge-paired particles. The corresponding experimental signatures are discussed.